Serovar-specific genomic features of Leptospira interrogans Hardjo: implications for host adaptation - Dubniewicz, Klaudia; Pardyak, Laura; Gurgul, Artur; Jasielczuk, Igor; Szmatoła, Tomasz; Arent, Zbigniew J. (Frontiers in Molecular Biosciences, 2025)
IntroductionLeptospirosis, caused by Leptospira spp., is one of the most widespread zoonoses worldwide. It affects both domestic and wild animals, with ruminants serving as a primary reservoir for serovar Hardjo. This serovar causes long-term colonisation of the kidney and genital tract. Hardjo strains are taxonomically assigned to two Leptospira species: Leptospira interrogans and Leptospira borgpetersenii. However, the molecular basis of L. interrogans serovar Hardjo adaptation remains poorly understood. Comparative genomic analysis of L. interrogans strains classified as the Hardjo serovar and other non-Hardjo serovars of the same species may help identify genetic determinants associated with host adaptation and species-specific cellular immune responses. Unfortunately, these pathogens are highly fastidious, and only a limited number of whole genomes have been sequenced to date.Materials and MethodsFour L. interrogans serovar Hardjo European isolates were sequenced. Using these new sequences alongside publicly available genomes of L. interrogans strains classified as Hardjo and non-Hardjo serovars, we performed comparative genomic analyses.ResultsHardjo strains formed a distinct phylogenetic clade and harboured unique variants, including an intact cas3 gene and a modified thiM start codon. We identified 88 Hardjo-specific orthologues, some located in putative genomic islands outside rfb locus. Several encoded proteins related to mobile elements, toxin–antitoxin systems or signal transduction. Enhanced biofilm formation in Hardjo strains supports a host-adapted phenotype.ConclusionThis study expands the genomic dataset for L. interrogans serovar Hardjo and provides novel insights into its genetic distinctiveness, suggesting potential factors that may facilitate colonisation and persistence in ruminant hosts.